Medication adherence and blood pressure control among hypertensive patients in Salyan Hospital - Sharma, Pradeep; Shrestha, Bikas (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Hypertension is a chronic medical condition with severe consequences and it remains inadequately managed everywhere. Medication adherence is a critical parameter for achieving strict blood pressure control in patients undergoing antihypertensive therapy. Good medication adherence is also a key factor determining the success of preventive measures for cardiovascular risk reduction. So, we aimed to study the medication adherence and blood pressure control among hypertensive patients of Salyan Hospital. Method: A cross-sectional observational study was conducted in Salyan Hospital. Total of 110 adult hypertensive patients were enrolled in the study. A structured questionnaire i.e. Morisky medication adherence questionnaire (MMAS-8) in Nepali version was used to measure adherence. In addition, WHO validated method of measuring BP, drug type used and type of therapy were also included. Data were entered and analyzed using IBM SPSS. Result: Out of 110 respondents enrolled, less than half of the respondents 45.45% had controlled BP. More than 4/5th were on monotherapy. BP control in monotherapy was 47.87% and in combination therapy was 45.45%. Patient with high, medium and low adherence were 40.9%, (44.54%) and 14.54% respectively. Level of adherence to antihypertensive drugs was related to BP control (p=0.0004). Most commonly used antihypertensive were CCBs. Conclusion: There was high prevalence of uncontrolled BP among hypertensive patients in Salyan Hospital. Similarly, higher number of patients were on monotherapy. But BP control in monotherapy and combination therapy was similar. Higher number of patients were non-adherent. The relation between BP control and medication adherence was statistically significant. So the causes of poor BP control and poor adherence should be explored and addressed in each doctor-patient encounter.